2019
DOI: 10.3390/md17020108
|View full text |Cite
|
Sign up to set email alerts
|

Eckol as a Potential Therapeutic against Neurodegenerative Diseases Targeting Dopamine D3/D4 Receptors

Abstract: The G protein-coupled receptor (GPCR) family of proteins comprises signaling proteins that mediate cellular responses to various hormones and neurotransmitters, and serves as a prime target for drug discovery. Towards our goal of discovering secondary metabolites from natural sources that can function as neuronal drugs, we evaluated the modulatory effect of eckol on various GPCRs via cell-based functional assays. In addition, we conducted in silico predictions to obtain molecular insights into the functional e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 46 publications
0
38
0
Order By: Relevance
“…Recently, we demonstrated that the selective h MAO-A inhibitor eckol, which contains phloroglucinol and dibenzo-1,4-dioxin elements, dose-dependently stimulates activity of D 3 R and D 4 R in a GPCR cell-based study with null effects on 5HT 1A , D 1 R, M 5 , NK 1 , and V 1A receptors [23]. Thus, we expected that phloroglucinol plays a role as a modulator of h MAOs and dopamine D 3 and D 4 receptors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we demonstrated that the selective h MAO-A inhibitor eckol, which contains phloroglucinol and dibenzo-1,4-dioxin elements, dose-dependently stimulates activity of D 3 R and D 4 R in a GPCR cell-based study with null effects on 5HT 1A , D 1 R, M 5 , NK 1 , and V 1A receptors [23]. Thus, we expected that phloroglucinol plays a role as a modulator of h MAOs and dopamine D 3 and D 4 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Strong intermolecular interactions between these phlorotannins and Asp103 and Phe288 residues of D 1 R may contribute to their antagonist effects. In the predicted D 3 R/D 4 R‒dieckol and D 3 R/D 4 R‒PFF-A complexes, phlorotannins strongly interacted with conserved OBP residues Asp110 in TM-3 and Ser192 in TM-5 of D 3 R (Asp115 in TM-3 and Ser197 in TM-5 of D 4 R) and were surrounded by hydrophobic residues of D 3 R/D 4 R. Similar to eckol [23], PFF-A hydrophobically interacted with the Phe346 residue of D 3 R via pi-pi stacked interaction, but dieckol could not interact with that residue due to the binding orientation. Instead of Phe346, dieckol strongly bound the Phe345 residue of D3R via pi-pi stacked interaction (Figure 6F).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The functional activity of the test compounds (agonist or antagonist) was evaluated by measuring their effects on cAMP modulation or Ca 2+ ion mobilization, depending on the receptor type. All assays were performed at Eurofins Cerep (Le Bois I'Eveque, France) following their in-house protocol, as stated in our previous reports [66][67][68].…”
Section: Cell-based Functional Gpcr Assaymentioning
confidence: 99%